2019
DOI: 10.3390/medicines6030077
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Transoral Laser Microsurgery in Benign, Premalignant and Malignant (Tis, T1, T2) Lesion of the Glottis. A Literature Review

Abstract: Carbon Dioxide transoral laser microsurgery represents a reliable option for the treatment of early glottic carcinoma (Tis–T2), with good functional and oncological outcomes, nowadays representing one of the main options in larynx preservation protocols. The development and improvement of laser devices means surgeons are able to use more precise instruments compared with classic cold dissection in laser-assisted phonosurgery. Secondary effects on voice, swallowing, or quality of life as well as complications h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…This population is limited to patients with good oral access and cervical spine mobility. As well, surgeon experience is a critical feature in determining the success of surgery . Patients with advanced T stage with cartilage involvement or transglottic spread would be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This population is limited to patients with good oral access and cervical spine mobility. As well, surgeon experience is a critical feature in determining the success of surgery . Patients with advanced T stage with cartilage involvement or transglottic spread would be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…As well, surgeon experience is a critical feature in determining the success of surgery. 37 Patients with advanced T stage with cartilage involvement or transglottic spread would be excluded. Certain authors showed a selection bias for patients with early T-stage disease.…”
Section: Meta-analysis and Database Comparisonmentioning
confidence: 99%
“…1,2 Transoral CO 2 laser microsurgery under anesthesia or in the setting of office laryngology in awake patients has been used for both benign and oncological laryngeal work. 5 Early laryngeal carcinoma can be successfully treated both with laser surgery and radiotherapy, yet the latter may have some undesirable long-term side effects, whereas laser cordectomy offers quick recovery and the possibility of second look when healthy margins are in doubt. Better and more accurate staging systems for endoscopic laser cordectomies have meant better understanding and communication between surgeons and pathologists.…”
mentioning
confidence: 99%
“…4,5 Different types of lasers offer different tissue manipulation and in some cases have a superior outcome in comparison to the standard CO 2 laser. 5 Diode laser, KTP, and PDL cause better photocoagulation and, by extension, better hemostasis. 2,6,7 Other technical characteristics, such as flexibility and portability, make these lasers preferable and more cost-effective in some cases of laryngeal surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation